Notarial certificate of wills in the conditions of recodification of civil legislation of Ukraine - Lukasevych-Krutnyk, Iryna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
The article is devoted to the study of notarization of wills in terms of recoding the civil legislation of Ukraine.  It clarifies the concept of a will as a unilateral transaction and the conditions of its validity, defines the range of entities authorized to certify wills, explores the general procedure for certification of wills by notaries.  A number of problems of modern judicial and notarial practice of application of the hereditary legislation which need the decision in the conditions of recodification of the civil legislation of Ukraine are covered.  The research was conducted on the basis of the analysis of doctrinal sources, the current legislation of Ukraine, materials of judicial practice.Conclusions of the article indicate that with the adoption of the Civil Code of Ukraine as the main codified act of civil law, the rules of inheritance law contained a number of novelties and were once one of the most progressive. However, the development of public relations, information technology and the need to approximate Ukrainian private law to European standards required the improvement of a number of provisions of inheritance law, including notarization of wills, and harmonization of judicial and notarial practice of inheritance law. Therefore, the recodification of the Civil Code of Ukraine in terms of inheritance law and updating the rules of special legislation governing notarization of wills is a unique opportunity to improve national legislation on inheritance, taking into account trends in EU legislation and national traditions and customs, which will promote proper protection of rights and interests of the participants of hereditary relations.